Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Doped 2D VX2 (X = S, Se, Te) monolayers as electrocatalysts for ammonia production: a DFT based study - Maibam, Ashakiran; BabaRao, Ravichandar; Krishnamurty, Sailaj A. (Applied Surface Science, 2022)
Electrocatalytic nitrogen fixation under ambient conditions on vanadium dichalcogenides (VX2) with non-metal dopants has been explored herein. Understanding the interface chemistry, inherent electronic and acute synergistic nature of non-metal dopants on two unique phases of VX2 has been meticulously explored through a scrutiny of several non-metal atoms as catalytic centers. The efficacity of N-2 chemisorption and N-N bond activation has been implemented as crucial parameters to realize boron and carbon doped VX2 monolayers to be electrocatalytically active for nitrogen reduction reaction (NRR). Detailed investigation on the NRR mechanism brings out the pivotal role of thermodynamic favourability for product formation obtained from Gibbs free energy differences. The charge transfer on N and pi-pi* orbital hybridization and electron ``donor-acceptor `` mechanism between the non-metal and N-2 has been found to modulate the electrocatalytic barrier for NRR on VX2 monolayers. This study proposes boron doped VS2 as an efficient chemically feasible, earth abundant sustainable electrocatalyst for NRR with an overpotential as low as 0.06 eV.
Keywords: 1T and 2H phases; DFT; electrocatalysts; Nitrogen Reduction Reaction; Non metal dopants; Vanadium dichalcogenides

High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting

Electrocatalytic nitrogen reduction on defective graphene modulated from single atom catalyst to aluminium clusters - Maibam, Ashakiran; Krishnamurty, Sailaja; BabaRao, Ravichandar (Applied Surface Science, 2023)
Density Functional Theory (DFT) investigation on the most earth-abundant Al-based catalysts, has been conducted detailing its electronic properties and catalytic efficacy for nitrogen reduction at ambient condition. The Al-based catalysts have been modulated to perform as par a highly performing, but rare, Ru-single atom catalytic center by varying number of Al atoms, shape, and size. The coalesce of band-center, work function and electronic properties in metal atom catalysts along with N-N bond activation has been demonstrated to be responsible for an efficient nitrogen reduction reaction (NRR) with Delta Gmax of 0.78 eV in Al5 supported on N-doped double vacancy graphene (Al5@N4-DVG) catalyst. Electron localization function analysis has shown a weak physisorption of N2 in the Al-based catalysts. Projected Density of States (PDOS) illustrates the enhancement of aluminium electron density in Al5@N4-DVG led to enhanced orbital densities overlap of Alp and Np electrons. The Bader charge analysis and electronic analysis of the intermediates show efficient electron gain on the N atoms, leading to formation of NH3 from the NxHy intermediates in Al5@N4-DVG catalyst.

Metal-organic framework-derived mesoporous B-doped CoO/Co@N-doped carbon hybrid 3D heterostructured interfaces with modulated cobalt oxidation states for alkaline water splitting - Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Kim, Tae Hyeong; Nam, Dong Hwan; BabaRao, Ravichandar; Lee, Seunghyun (Small, 2023)
Heteroatom-doped transition metal-oxides of high oxygen evolution reaction (OER) activities interfaced with metals of low hydrogen adsorption energy barrier for efficient hydrogen evolution reaction (HER) when uniformly embedded in a conductive nitrogen-doped carbon (NC) matrix, can mitigate the low-conductivity and high-agglomeration of metal-nanoparticles in carbon matrix and enhances their bifunctional activities. Thus, a 3D mesoporous heterostructure of boron (B)-doped cobalt-oxide/cobalt-metal nanohybrids embedded in NC and grown on a Ni foam substrate (B-CoO/Co@NC/NF) is developed as a binder-free bifunctional electrocatalyst for alkaline water-splitting via a post-synthetic modification of the metal-organic framework and subsequent annealing in different Ar/H-2 gas ratios. B-CoO/Co@NC/NF prepared using 10% H-2 gas (B-CoO/Co@NC/NF [10% H-2]) shows the lowest HER overpotential (196 mV) and B-CoO/Co@NC/NF (Ar), developed in Ar, shows an OER overpotential of 307 mV at 10 mA cm(-2) with excellent long-term durability for 100 h. The best anode and cathode electrocatalyst-based electrolyzer (B-CoO/Co@NC/NF (Ar)(+)//B-CoO/Co@NC/NF (10% H-2)(-)) generates a current density of 10 mA cm(-2) with only 1.62 V with long-term stability. Further, density functional theory investigations demonstrate the effect of B-doping on electronic structure and reaction mechanism of the electrocatalysts for optimal interaction with reaction intermediates for efficient alkaline water-splitting which corroborates the experimental results.
Keywords: 3D heterostructures; B-doped metal-oxides; electrocatalysts; hydrogen evolution reactions; metal-organic frameworks; oxygen evolution reactions

Robust zeolitic tetrazole framework for electrocatalytic dopamine detection with high selectivity - Sarfudeen, Shafeeq; Sruthi, Vadakke Purakkal; Maibam, Ashakiran; Panda, Premchand; Jhariat, Pampa; Senthilkumar, Sellappan; BabaRao, Ravichandar; Panda, Tamas (Inorganic Chemistry, 2023)
A novel zeolitic tetrazolate framework (ZTF-8) has been synthesized by solvent-free heat-assisted (70 C-degrees) mechanochemical grinding of zinc acetate and 5-methyl tetrazole in the presence of NaOH powder. The structure of ZTF-8 adopts the zeolitic sodalite (SOD) topology with uncoordinated N-heteroatom sites and resembles the structure of the well-known zeolitic imidazole framework ZIF-8. ZTF-8 is exceptionally stable in 0.1 M aqueous acid and base solutions for 60 days at 25 C-degrees. The unique structure with uncoordinated N-heteroatom active sites and exceptional stability of ZTF-8 facilitated the electrocatalytic oxidation of dopamine to dopamine quinone at neutral pH. Without any postsynthetic modification, ZTF-8 is directly used for the facile electrochemical detection of dopamine over a wide range of concentrations (5-550 mu M) with a high sensitivity (2410.8 mu A mM-1 cm-2). It also demonstrated promising selectivity over other interferents of similar oxidation potential, such as ascorbic acid and uric acid. The DFT study revealed that the ZTF-8 framework has a higher binding energy (-145.07 kJ/mol) and stronger interaction with dopamine than its isostructural ZIF-8 structure (-130.42 kJ/mol).

Breaking the inactivity of MXenes to drive Ampere-level selective oxygen evolution reaction in seawater - Gbadamasi, Sharafadeen; Loomba, Suraj; Haris, Muhammad; Khan, Muhammad Waqas; Maibam, Ashakiran; Mousavi, Seyed Mahdi; Mahmud, Sofiu; Thomsen, Lars; Tadich, Anton; BabaRao, Ravichandar; Xian, Jian; Mahmood, Nasir (MATERIALS SCIENCE & ENGINEERING R-REPORTS, 2024)
Keywords: 2D heterostructures; Metal-organic framework; Oxygen Evolution Reaction

Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis

Metal-organic frameworks for enhanced hydrogen generation from syngas: a density functional theory approach - Gopalsamy, Karuppasamy; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; BabaRao, Ravichandar (CHEMPLUSCHEM, 2024)
Keywords: carbon capture; H-2 separation; Metal organic; Porous coordination network (PCN-250); Syngas

Purification of waste-generated biogas mixtures using covalent organic framework's high CO2 Selectivity - Paul, Ratul; Maibam, Ashakiran; Chatterjee, Rupak; Wang, Wenjing; Mukherjee, Triya; Das, Nitumani; Yellappa, Masapogu; Banerjee, Tanmay; Bhaumik, Asim; Venkata Mohan, S.; BabaRao, Ravichandar; Mondal, John (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: CAPTURE; CARBON-DIOXIDE; Efficiency; Energy; Hydrogen; STORAGE

Surface electronic properties-driven electrocatalytic nitrogen reduction on metal-conjugated porphyrin 2D-MOFs - Maibam, Ashakiran; Orhan, Ibrahim B.; Krishnamurty, Sailaja; Russo, Salvy P.; BabaRao, Ravichandar (ACS Applied Materials and Interfaces, 2024)
Two-dimensional (2D) metal organic framework (MOF) or metalloporphyrin nanosheets with a stable metal-N-4 complex unit present the metal as a single-atom catalyst dispersed in the 2D porphyrin framework. First-principles calculations on the 3d-transition metals in M-TCPP are investigated in this study for their surface-dependent electronic properties including work function and d-band center. Crystal orbital Hamiltonian population (-pCOHP) analysis highlights a higher contribution of the bonding state in the M-N bond and antibonding state in the N-N bond to be essential for N-N bond activation. A linear relationship between Delta G(max) and surface electronic properties, N-N bond strength, and Bader charge has been found to influence the rate-determining potential for nitrogen reduction reaction (NRR) in M-TCPP MOFs. 2D Ti-TCPP MOF, with a kinetic energy barrier of 1.43 eV in the final protonation step of enzymatic NRR, shows exclusive NRR selectivity over competing hydrogen reduction (HER) and nitrogenous compounds (NO and NO2). Thus, Ti-TCPP MOF with an NRR limiting potential of -0.35 V in water solvent is proposed as an attractive candidate for electrocatalytic NRR.
Keywords: Density Functional Theory (DFT); electrocatalytic nitrogen reductionreaction; kinetic energy barrier; limitingpotential; Metalloporphyrin; NRR selectivity

Synthesis of Hofmann-based metal-organic frameworks incorporating a bis-pyrazole linker for various gas separations - Matthews, Brooke L.; Harvey-Reid, Nathan C.; Jangodaz, Elnaz; Scott, Victoria-Jayne; Polson, Matthew I. J.; Maibam, Ashakiran; BabaRao, Ravichandar; Telfer, Shane G.; Kruger, Paul E. (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: acetylene; C2H2/CH4; Ni; Purification; SPIN-CROSSOVER BEHAVIOR